h - Nitaj, Abderrahmane; Pointcheval, David; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 4th International Conference on the Theory and Application of Cryptographic Techniques in Africa, AFRICACRYPT 2011, held in Dakar, Senegal, in July 2011. The 23 papers presented together with abstracts of 3 invited talks were carefully reviewed and selected from 76 submissions. They are organized in topical sections on protocols, cryptanalysis, secret-key cryptography, efficient implementations, cryptographic schemes, algorithmic problems, elliptic curves, fault analysis, and security proofs.
Keywords: Computer science; Computer Communication Networks; Operating systems (Computers).; Data protection; Data encryption (Computer science).; Computer software; Information Systems; Computer Science; Data Encryption; Computer Communication Networks; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Systems and Data Security; Operating Systems